2011
DOI: 10.1097/tp.0b013e3181fe131b
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Sirolimus-Based Immune Suppression After Liver Transplantation Is Safe and Effective: A Single-Center Experience

Abstract: Sirolimus was safe and may improve outcome in selected patients after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…The incidence of HAT related to sirolimus use varies in different reports. Molinari et al [78] reported a higher incidence of HAT in sirolimus group with CNI group but no HAT was reported in LT recipients on sirolimus in another study by Harper et al [79] . Similar results were reported by Fischer et al [80] , and they did notice no HAT following conversion of CNIs to everolimus.…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…The incidence of HAT related to sirolimus use varies in different reports. Molinari et al [78] reported a higher incidence of HAT in sirolimus group with CNI group but no HAT was reported in LT recipients on sirolimus in another study by Harper et al [79] . Similar results were reported by Fischer et al [80] , and they did notice no HAT following conversion of CNIs to everolimus.…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…Sirolimus is most commonly used to suppress the immune system and prevent rejection after kidney transplant; however, it is also used as an immune suppressant after other organ (liver, heart, and lung) and bone marrow transplants. [54][55][56][57][58][59] Sirolimus and other rapalogs associate with binding protein FKBP12, primarily blocking the mTORC1 complex with little to no activity against the mTORC2 complex. [60] Newer second-generation small molecule inhibitors of mTOR kinase that target both mTORCl and mTORC2 (mTORC1/2 inhibitors) are under development (see section 3.2).…”
Section: Rapalogsmentioning
confidence: 99%
“…Current work shows that sirolimus causes a significant decrease in acute rejection and improvement in patient and graft survival compared to azathioprine [21,22].…”
Section: Adjuvant Agentsmentioning
confidence: 99%
“…After induction therapy, whether this involves high-dose steroids that are then tapered off or an anti-thymocyte globulin preparation, maintenance therapy involves maintaining the program of conventional immunosuppression in order to prevent graft rejection [21]. Conventional maintenance therapy has evolved over the years and now includes multiple immunosuppressive agents that are given in non-toxic doses.…”
Section: Maintenance Strategymentioning
confidence: 99%